Such Hardworking People: Italian Immigrants in Postwar Toronto - Iacovetta, Franca (McGill-Queen's studies in ethnic history, 1993)
During the last century, 26 million Italian women, men, and children have traded an uncertain future in Italy for the prospect of a better life elsewhere. Canada has long been home to Italian immigrants, but in the years just after the Second World War they began to arrive in multitudes. Toronto emerged as the most popular Canadian destination and now, with more than 400,000 residents of Italian heritage, has one of the largest Italian populations outside Italy. Franca Iacovetta describes the working-class experiences of those who came to Toronto from southern Italy between 1946 and 1965, focusing on the relations between newly arrived immigrant workers and their families." "The Italians who came to Toronto before 1965 were predominantly young, healthy women and men eager to secure jobs and prepared to make sacrifices in order to secure a more comfortable life for themselves and their children. Franca Iacovetta examines the changes many of them had to face during the transition from peasant worker in an under-developed, rural economy to wage-earner in an urban, industrial society." "Although both women and men had to struggle and were exploited, Iacovetta shows that they found innovative ways to recreate cherished rituals and customs from their homeland and to derive a sense of dignity and honour from the labours they performed." "Such Hardworking People is informed by a feminist analysis. Iacovetta shows that for both sexes work patterns and experiences, as well as self-perceptions, were influenced by domestic responsibilities and gender relations within the household and by the labour market, employer strategies, and kin-linked networks of support. In addition to conducting numerous interviews with some of the immigrants, she has drawn on recent scholarship in immigration, family, labour studies, oral history, and women's history. --Publisher's description
Keywords: Canadiens d'origine italienne Ontario Toronto Conditions sociales; Foreign workers, Italian; Foreign workers, Italian Ontario Toronto; Immigrants Ontario Toronto Conditions sociales; Immigrants Ontario Toronto Social conditions; Immigrants Social conditions; Italian Canadians Ontario Toronto Social conditions; Italians Ontario Toronto Social conditions; Italians Social conditions; Italiens Ontario Toronto Conditions sociales; Ontario Toronto; Travailleurs étrangers italiens Ontario Toronto

Gender Conflicts: New Essays in Women's History - Iacovetta, Franca; Valverde, Mariana (Social history of Canada, 1993)
In the early 1970s, when women's history began to claim attention as an emerging discipline in North American universities, it was dominated by a middle-class Anglo-Saxon bias. Today the field is much more diverse, a development reflected in the scope of this volume. Rather than documenting the experiences of women solely in a framework of gender analysis, its authors recognize the interaction of race, class, and gender as central in shaping women's lives, and men's. These essays represent an exciting breakthrough in women's studies, expanding the borders of the discipline while breaking down barriers between mainstream and women's history. --Publisher's description. Contents: When the mother of the race is free': Race, reproduction, and sexuality in first-wave feminism / Mariana Valverde -- Maidenly girls' or 'designing women'? The crime of seduction in turn-of-the-century Ontario / Karen Dubinsky -- The 'hallelujah lasses': Working-class women in the Salvation Army in English Canada, 1882-92 / Lynne Marks -- The alchemy of politicization: Socialist women and the early Canadian left / Janice Newton -- Wounded womanhood and dead men: Chivalry and the trials of Clara Ford and Carrie Davies / Carolyn Strange -- Class, ethnicity, and gender in the Eaton strikes of 1912 and 1934 / Ruth A. Frager -- 'Feminine trifles of vast importance': Writing gender into the history of consumption / Cynthia Wright -- Making 'new Canadians': Social workers, women, and the reshaping of immigrant families / Franco Iacovetta.